Baylor and Siliman historical and academic comparison of two Christian universities (2011)
Employing historical and comparative approaches, this paper describes how Christian commitment has inspired Baylor University and Siliman University in establishing quality higher education institutions that have surpassed the test of time and continued to develop academic and community programs that bear and transmit Christian values and ideals to students amidst the secularization of higher education in the world. Informed by their vision and mission, both institutions demonstrated efforts in promoting faith-learning integration and at the same time ensuring quality education at par with other universities in the US and the Philippines, respectively. Certainly, the younger Siliman still has something to learn from Baylor although it has its own ways of integrating faith and learning and in improving the quality and scholarships of its faculty and students, evident in the recognition it received in recent years.
Keywords: Christian University